Psycho-Social Behavior of the Child Diabetes Diagnosed in the Favorite Family and Placement Center: Array - Ștefanescu, Cristina (New Trends in Psychology, 2020)
We present the psychosocial behavior of a 10-year-old girl who was diagnosed with type 1 diabetes at the age of 5. It comes from an underprivileged family, having four older siblings and being neglected by parents. Her mother left to work abroad and her father worked temporarily in the village where they lived. Recently the father died. He arrived at the Emergency Clinic Hospital for Galati Children countless times, with a long history of hospitalizations. The girl took advantage of the disease to escape school and poverty at home. At the hospital she received hot food and befriended children of her age. He refused to eat for a day, which deliberately caused him to be hospitalized and hospitalized. The girl is insulin dependent. When he met with the clinical psychologist he demonstrated emotional immaturity, lack of cooperation and showed no trace of regret that his father died. Meanwhile, the mother agreed to let the child go to a placement center. After arriving at the placement center where he made friends, the number of admissions decreased and the girl was no longer absent from school.